2014
DOI: 10.1155/2014/561456
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSynergistic Effect of Curcumin in Combination with Third Generation Cephalosporins against Bacteria Associated with Infectious Diarrhea

Abstract: Diarrhea is one of the leading causes of morbidity and mortality in humans in developed and developing countries. Furthermore, increased resistance to antibiotics has resulted in serious challenges in the treatment of this infectious disease worldwide. Therefore, there exists a need to develop alternative natural or combination drug therapies. The aim of the present study was to investigate the synergistic effect of curcumin-1 in combination with three antibiotics against five diarrhea causing bacteria. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 31 publications
2
29
1
3
Order By: Relevance
“…The activity was time- and dose-dependent, and 100% killing was achieved at 50  μ M (equivalent to 18.42  μ g/mL) after 2 hr exposure [30]. In contrast, Sasidharan et al [41] showed that the same compound had a MIC of 250  μ g/mL against S. aureus , which is comparable to the native curcumin [8, 9]. In an in vivo mouse model, administration of 100 mg/kg curcumin was shown to protect the mice infected with both MSSA and MRSA from pneumonia by targeting the α -hemolysin (HIa) protein of S. aureus [40].…”
Section: Curcumin-mediated Inhibition Of S Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity was time- and dose-dependent, and 100% killing was achieved at 50  μ M (equivalent to 18.42  μ g/mL) after 2 hr exposure [30]. In contrast, Sasidharan et al [41] showed that the same compound had a MIC of 250  μ g/mL against S. aureus , which is comparable to the native curcumin [8, 9]. In an in vivo mouse model, administration of 100 mg/kg curcumin was shown to protect the mice infected with both MSSA and MRSA from pneumonia by targeting the α -hemolysin (HIa) protein of S. aureus [40].…”
Section: Curcumin-mediated Inhibition Of S Aureusmentioning
confidence: 99%
“…Upper panel shows the structure of curcumin-1 [30, 41] while the lower panel shows the metal complexes of curcumin, indium curcumin [42, 43]. The chemical structures above were drawn using a free online tool, ChemWriter (http://chemwriter.com/).…”
Section: Figurementioning
confidence: 99%
“…[ 5 ] Recently, its antibacterial action is found to be synergistic with several antibiotics. [ 6 7 ] However, there is limited research data on this synergistic antibacterial action of curcumin, especially against biofilm producing organisms to support its benefits in biofilm-associated infections. We conducted this study to determine the in vitro synergy of curcumin with antibiotics against biofilm producing clinical bacterial isolates.…”
Section: Introductionmentioning
confidence: 99%
“…3). 35 However, the CUR used in our studies recorded a MIC of 2 mg mL À1 . 34 CUR is antibacterial, and according to the literature, the minimum inhibitory concentration (MIC) ranges between 0.25 and 0.5 mg mL À1 .…”
Section: Resultsmentioning
confidence: 79%